Infâncias queer nos entre-lugares de um currículo: a invenção de modos de vida transviados - João Paulo de Lorena Silva (2018)
Queer infants populate the school curriculum. These are childhoods that, because they do not meet the regulatory norms of gender and sexuality, are read as deviant, monstrous and abnormal. Such childhoods are not recognized by the standards of intelligibility that institute what is to be infantile in our time. This master's dissertation analyzes what the curriculum does with the children who experience this childhood and the movements of resistance and creation of possible that the infantile queer forge in the curricular territory. Working with concepts drawn from post-critical curriculum theories, queer studies and philosophies of difference by Michel Foucault and Gilles Deleuze, the general argument of this dissertation is that queer childhoods are present in the school curriculum, resisting gender norms and creating ways of life deviant. These ways of life are characterized by a transient and deviant attitude towards the gender-sexuality system and find in queer friendship a place of survival, creation, and dissemination of possible. These childhoods are crossed and made up of three different lines: the line of precariousness (abject childhood), the line of aesthetics (childhood that scares and fascinates) and the line of politics (childhood that fights and resists). They are infants who, in an attitude of refusal to the masculinities and femininities that are imposed on them as natural and recognizable, choose to live in another way, deviant, and minority. These ways of life, invented by queer children, though traversed by the sign of abjection, draw and disseminate in the curriculum the joy and power of another childhood, which breaks gender-form and makes the difference proliferate. The research was carried out in a public school in Belo Horizonte, with classes from the first years of elementary school, using, as a methodological resource, the cartography and the queer analysis of the information produced in the field.